2018
DOI: 10.1038/s41598-018-34156-6
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of maltol on cisplatin-induced nephrotoxicity through the AMPK-mediated PI3K/Akt and p53 signaling pathways

Abstract: Cisplatin, a potent anticancer drug, is usually causing nephrotoxicity; limiting its therapeutic application and efficiency. Maltol may be used to prevent such toxic effect. The aim of this study was to investigate the underlying protective mechanisms of maltol on nephrotoxicity by cisplatin using a cisplatin-treated mouse model and a cellular toxicity model of HEK293 cells. The blood urea nitrogen (BUN), creatinine (CRE) and neutrophil gelatinase-associated lipocalin (NGAL) levels in mice were increased by ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 48 publications
12
50
0
Order By: Relevance
“…Although the mechanisms involved in acute renal failure have not been clearly identified, the inflammatory response induced by macrophage activation is recognized as an important cause [ 3 , 4 ]. Recent experimental evidence has revealed that changes in the inflammatory response are involved in the pathophysiological mechanism underlying cisplatin-induced renal toxicity [ 5 , 6 ], and the need for further relevant studies has been emphasized. Previous studies have shown that bee venom and its active ingredient phospholipase A2 (PLA2) could increase the number of regulatory T cells (Tregs) to inhibit acute injury to the kidney and liver.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanisms involved in acute renal failure have not been clearly identified, the inflammatory response induced by macrophage activation is recognized as an important cause [ 3 , 4 ]. Recent experimental evidence has revealed that changes in the inflammatory response are involved in the pathophysiological mechanism underlying cisplatin-induced renal toxicity [ 5 , 6 ], and the need for further relevant studies has been emphasized. Previous studies have shown that bee venom and its active ingredient phospholipase A2 (PLA2) could increase the number of regulatory T cells (Tregs) to inhibit acute injury to the kidney and liver.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of urinary creatinine, BUN and NAG were significantly elevated in the CDDP 3-day and CDDP 5-day groups compared to the control group (Figs 1 and 2 ). Tubulointerstitial injury, such as tubular cell atrophy and cell infiltration [ 34 , 35 ] were observed in the PAS-stained kidney sections of the mice treated with CDDP.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that murine double minute 2 (MDM2), the downstream effector molecule of PI3K/Akt, is involved in the regulation of proliferation, and the interaction of MDM2, Bcl‐2 family proteins, and p53 play an important role in the p53 transcription‐independent apoptosis pathway (Chi, 2014). Activation of Akt/Bcl‐2/Bax signaling promotes cell growth (C. Wang, Yao, Xu, & Zheng, 2016), which may be achieved by inhibiting p53, regulating the expression of Bcl‐2/Bax through the downstream effect of PI3K/Akt to promote proliferation and antiapoptosis (Chang et al, 2017; Mi et al, 2018; X. Li, Miao, Wang, Xu, & Li, 2015; Zhang, Wu, Liu, Tian, & Qu, 2015). It indicates that FSTL1 activates AMPK/PI3K/Akt signaling pathway can inhibit p53 expression and upregulate Bcl‐2 expression, which is important for inhibiting cardiomyocyte apoptosis and promoting cardiomyocyte proliferation.…”
Section: Mechanism Of Fstl1 Regulating Cardiomyocyte Proliferationmentioning
confidence: 99%